Peningkatan kemampuan berpikir kritis siswa melalui penerapan KIT listrik berbasis STEAM kontekstual - Putri Rahmaddani; Fakhruddin Z; Nur Islami; Retni Khairina (Universitas Sultan Ageng Tirtayasa, 2023)
The nation's current generation must master 21st-century skills, including critical thinking skills, to face today's world competition with rapid technological advances. This contextual STEAM-based electrical KIT aims to describe students' necessary thinking abilities and discover the differences in critical thinking abilities between the experimental and control classes. The design used in the study, namely the post-test-only control group and the type of quasi-experimental research. This study included all class IX students of SMP Muhammadiyah Kuok TA.2022/2023 as a population. A sample of 47 students consisted of class IX.1 as the experimental group and category IX.2 as the control group. Posttest critical thinking skills in dynamic electricity material comprised 12 multiple choice questions previously tested for validity and reliability as a data collection instrument. The average posttest results of students' critical thinking skills were used for descriptive analysis with SPSS version 25, and normality, homogeneity, and hypothesis tests were used for inferential analysis. This study shows that students' critical thinking skills regarding dynamic electricity material can be improved by applying contextual STEAM-based electricity KIT contextual learning. This can be seen in the average value obtained in the experimental class is better than the control class.